Good Luck Animal Amulets in Thai Magazines : Contemporary Thai Social Values - Sanpinit, Pattaradhorn (Journal of Cultural Approach, 2022)
This research aims to analyze social values by exploring and classifying animal amulets in contemporary Thai Magazines by focusing on amulet qualities and the language used. The gathered information was from Thai publications between March and June of 2021. The study is qualitative in nature. The results shows that there are 18 animal amulets, most of them contain folk Buddhism. The animal amulets are distinguished by the animal’s skills as well as its names and qualifications. This corresponds to the preferences of the Thai individual. In Thailand, people value fortune and money, having a satisfying job that pays well and being healthy. The amulets are also said to improve sex appeal or great mercy, good physical health, safety and the value of honoring authority. According to research, individuals are increasingly trying to rely on amulets to improve their quality of life in a materialistic world. Thus, it is still an effective instrument in encouraging social value. Animal amulets reflect contemporary Thai society, which rely on amulets, value money and material prosperity rather than embracing religious teachings. As a result, this study examined the relationship between amulets and worship to meet the needs and values of current Thai society.